Determination of Bioactive Compounds and Antioxidant Capacity in Leaf and Pulp of Annona muricata - Mario Alberto Ruiz-López; Belinda Vargas-Guerrero; J. de Jesús Vargas-Radillo; Efigenia Montalvo-González; Eduardo Salcedo-Pérez; Ramon Rodriguez-Macias; Carmen Magdalena Gurrola-Diaz; Pedro Macedonio García-López; Juan Carlos Pizano-Andrade (Chemistry)
This study focused on analyzing and comparing bioactive compounds, specifically phenolics, in the pulp and leaf of Annona muricata (soursop), a crop highly valued in Latin America for its culinary and traditional uses. Methanolic extractions of leaf and pulp were performed for phytochemical screening, high-performance liquid chromatography (HPLC), and measurements of antioxidant capacity. The results confirmed the presence of 15 phenolic compounds in the leaf and 14 in the pulp; these included phenolic acids and flavonoids. Shikimic acid was the main component identified, constituting 85 mg/g of the dry leaf sample and 17.50 mg/g of the dry pulp. The antioxidant capacity was determined using DPPH and FRAP. The percentages of inhibition were 70.93 and 15.10 in the leaf and pulp, respectively. This work expands our knowledge about the compounds present in A. muricata, which may be partly responsible for the known benefits of this plant for human health and nutrition.